Contribution of Cation Addition to MnO2 Nanosheets on Stable Co3O4 Nanowires for Aqueous Zinc-Ion Battery - Wang, Nengze; Yang, Gaochen; Gan, Yi; Wan, Houzhao; Chen, Xu; Wang, Cong; Tan, Qiuyang; Ji, Jie; Zhao, Xiaojuan; Liu, Pengcheng; Zhang, Jun; Peng, Xiaoniu; et al. (Frontiers in Chemistry, 2020)
Zinc-based electrochemistry attracts significant attention for practical energy storage owing to its uniqueness in terms of low cost and high safety. In this work, we propose a 2.0 V high voltage and wearable Zn–MnO2 battery with core@shell Co3O4@MnO2 on current collector of carbon cloth as a cathode, an optimized aqueous ZnSO4 electrolyte with Mn2+ additive and a Zn metal anode. Benefitted from the architecture engineering of growing Co3O4 nanorods on carbon cloth and subsequently deposited MnO2 on Co3O4, with a two–step hydrothermal methods, the binder-free and flexible zinc-ion battery delivers a high power of 2384.7 W kg−1, a high capacity of 245.6 mAh g−1 at 0.5 A g−1, and a high energy density of 212.8 Wh kg−1. It is found that the Mn2+ cations are in situ converted to Mn3O4 during electrochemical operations followed by a phase transition into electroactive MnO2 in our battery system. The charge-storage mechanism of the MnO2-based cathode is Zn2+/Zn and H+ insertion/extraction. This work shines light on designing multivalent cation-based battery devices with high output voltage, safety and remarkable electrochemical performances.